1998
DOI: 10.1002/(sici)1099-0496(199808)26:2<113::aid-ppul7>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

One-year follow-up of young children hospitalized for wheezing: the influence of early anti-inflammatory therapy and risk factors for subsequent wheezing and asthma

Abstract: We investigated the 1‐year outcome of children hospitalized for wheezing, paying special attention to the effect of early anti‐inflammatory therapy. In addition, we identified risk factors for recurrent wheezing and asthma. Eighty‐eight children under 2 years old treated in the hospital for wheezing were followed for 1 year. Nebulized anti‐inflammatory therapy was given for 16 weeks: 31 patients received budesonide, 29 patients cromolyn sodium, and 28 control patients received no therapy. The number of subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 30 publications
1
20
0
1
Order By: Relevance
“…[19] In addition, recent controlled clinical trials have failed to show any subsequent long-term benefi ts of ICS after the discontinuation of the treatment in less than 24-month-old children. [20][21][22] Despite long-term benefi ts were lacking, ICSs diminished wheezing symptoms as long as they were consumed, [20,21] which is in line with the present results at the population level. Regional treatment policies seem to exert infl uence on the hospitalization rates, indicating the role of ICSs in the prevention of asthma exacerbations in young children (Table 3).…”
Section: World Journal Of Pediatricssupporting
confidence: 90%
“…[19] In addition, recent controlled clinical trials have failed to show any subsequent long-term benefi ts of ICS after the discontinuation of the treatment in less than 24-month-old children. [20][21][22] Despite long-term benefi ts were lacking, ICSs diminished wheezing symptoms as long as they were consumed, [20,21] which is in line with the present results at the population level. Regional treatment policies seem to exert infl uence on the hospitalization rates, indicating the role of ICSs in the prevention of asthma exacerbations in young children (Table 3).…”
Section: World Journal Of Pediatricssupporting
confidence: 90%
“…Finnish studies have found that 4 months of treatment with nebulized budesonide reduced the recurrence of wheezing initially [89]. However, the beneficial effect disappeared shortly after termination of the treatment (the children had a mean age of 10.6 months at inclusion and RSV had been detected in 26%) [104]. In addition, the antiinflammatory therapy had no influence on the occurrence of asthma 3 yrs later [105].…”
Section: Obstructive Airway Diseases After Rsv Bronchiolitismentioning
confidence: 99%
“…14 This cohort has been evaluated in several followup visits from early childhood to adolescence. 14 This cohort has been evaluated in several followup visits from early childhood to adolescence.…”
mentioning
confidence: 99%